E-061 What's the Reliability and Significance of Pre-coiling CT Angiography in Ruptured Cerebral Aneurysms?. (29th July 2016) - Sung, J; Lee, D; Kim, S; Lee, H; Lee, S
Abstract : Purpose: The endovascular coiling of cerebral aneurysm is fundamentally based on exact evaluation of aneurysm size, shape and so-called working angle of procedure. Nowadays, as initial surveillance procedures, CT angiography has been performed prior to endovascular coiling of ruptured aneurysms. We retrospectively compared the initial CT angiography and initial working angle angiography focusing to interval changes, chosen treatment modality and its results. Material and methods: One hundred twenty two patients, each with ruptured cerebral aneurysm(s), underwent endovascular coiling procedure between 2012 Jan and 2014 Nov. Immediately after recognition of subarachnoid hemorrhage (SAH) symptom or mental change, CT angiography was checked as initial diagnostic procedure. After confirmation of SAH, catheter angiography was performed for decision making. We compared the CT angiography and catheter angiography and subgrouping was performed same as follows; Group 1 = no changes, group 2 = smaller aneurysm at catheter angiography, group 3 = larger aneurysm at catheter angiography. Results: The mean age was 53.9 years and female patients were dominant (80 cases). The mean interval of getting first image between CT angiography and catheter angiography was 115 minutes. Group 1 was 107 cases (87.7%). Group 2 was 11 cases (9.0%). Group 3 was 4 cases (3.3%). In group 2, the specific aneurysm location did not exist. Rather, "narrow neck with saccular dome" pattern was dominant (6 cases; 54.5% of group 2). The coiling procedures were successful in 9 cases (81.8%) in group 2, and one case of failed coiling showed typical discrepancy between CT angiography and catheter angiography. In group 3, specific aneurysm location could be found definitely; the dorsal wall of internal carotid artery was dominant (3 cases; 75% of group 3). In both groups, coiling procedures could be performed effectively based on working angle angiography as well as CT angiography. Conclusion: The discordance between CT angiography and catheter angiography was infrequent, but in these cases, mutual supplement is critical for exact decision making and safe endovascular coiling procedure. The CT angiography should be performed with same importance of working angle angiography. Disclosures: J. Sung: None. D. Lee: None. S. Kim: None. H. Lee: None. S. Lee: None.